15分之11+15分之4/(1又9分之4-3分之2*6分之5)
2个回答
15分之11+15分之4/(1又9分之4-3分之2*6分之5)
=15分之11+15分之4/(9分之13-9分之5)
=15分之11+15分之4/9分之8
=15分之11+15分之4/9分之8
=15分之11+10分之3
=30分之31
相关问题
15分之4-(9分之4-15分之11) 3分之2+8分之3-6分之1 7分之4+6分之1+7分之3
19分之3-15分之7+15分之7 12分之7+11分之6+12分之1+11分之5 6分之5-9分之4+6分之1-9分之
4=3又2分之()=2又3分之()=1又4分之几=5分之几 6又11分之4=()11分之15 13又20分之3=()20
2-12分之5-36分之11 4分之5-(4分之3-6分之1) 4分之5-(15分之4+3分之1
11分之5x[(5分之2+3分之1)/6分之5] 15分之4+15分之11/5分之3 44分之27x43
[9又2分之1+(-8又30分之1)]+[(-9又4分之3)+(-5又15分之4)]
2又4分之1x=3又8分之5 15分之2x+5分之3=3.6乘2又9分之1 1除(15分之1+x)=3
-4×(-6分之5-5分之1+1又4分之1-12分之11)×15
简算0.7*1又9分之4+2又4分之3*15+0.7*9分之5+4分之1*15
简便法计算.5分之6-9分之2-9分之7 6分之5+15分之4+15分之1+6分之7